Интимная лирика: новые стихотворения / Тимур Кибиров - Кибиров Тимур Юрьевич (Пушкинский фонд, 1998)
Экземпляры: аб. (2001) / Инвентарный номер: 43447 / Цена: / Сис.шифр: 84(2Pос=Рус)6-5 / Авт.знак: К 38 / ГРНТИ: 17.82.10 / ББК: 84(2Pос=Рус)6-5